ʻItipisō phakhawā - ʻAphinat Kitiphan,Pračhit Yotsunthō̜n (Bō̜risat ʻAmarinphrinting ʻǣn Phaplitching Čhamkat (Mahāchon), 2014)
Cremation volume for Pračhit Yotsunthō̜n, 1919-2014, former Thai banker, ประจิตร ยศสุนทร, Nangsư̄ ‘Anusō̜n ngānsop
Thīralưk nai ʻōkāt thī Somdet Phrathēprattanarātchasudā– Sayāmbō̜rommarātchakumārī sadet phrarātchadamnœ̄n mā nai kānphrarātchathān phlœ̄ng sop Nāi Pračhit Yotsunthō̜n Pō̜.Chō̜., Pō̜.Mō̜., Thō̜.Čhō̜.Wō̜. na mēn Wat Phrasīmahāthātwō̜ramahāwihān, Khēt Bāng Khēn, Krung Thēp Mahā Nakhō̜n, Wanʻāthit thī 5 Tulākhom Phutthasakkarat 2557
Keywords: Biografie; Festschrift; Cremation Volume